Breast Cancer Diagnosis: Cascade Reaction in Human Live Tissue Allows Clinically Applicable Diagnosis of Breast Cancer Morphology (Adv. Sci. 2/2019). Issue 2 (22nd January 2019) - Tanei, Tomonori; Pradipta, Ambara R.; Morimoto, Koji; Fujii, Motoko; Arata, Mayumi; Ito, Akihiro; Yoshida, Minoru; Saigitbatalova, Elena; Kurbangalieva, Almira; Ikeda, Jun‐ichiro; Morii, Eiichi; Noguchi, Shinzaburo; et al.
Abstract : In article number1801479, Shinzaburo Noguchi, Katsunori Tanaka, and co‐workers use a click‐to‐sense probe to detect acrolein, which is universally produced by cancer cells under oxidative stress, within five minutes at room temperature. All cancer types tested are imaged and discriminated through multiple cascade reactions in the living tissue of human patients. This probe can be used to quickly and accurately diagnose cancer morphology during breast‐conserving surgery, by reforming the conventional pathological methods.